Research on data access control algorithm based on fine-grained cloud storage. (4th June 2020) - Xu, Qiaoge
In order to ensure the cloud storage security and achieve fine-grained data access control, a new fine-grained data access control algorithm is established based on CP-ABE algorithm. The basic theory of CP-ABE algorithm is studied in depth, and then the fine-grained cloud storage controlling scheme based on digital envelope is put forward. The new scheme construction process is given, and then the corresponding algorithm is designed. Simulation analysis is carried out, results show that the proposed data access control algorithm can effectively improve the searching efficiency of cipher text, and achieve fine-grained access under cloud storage environment.